Pengembangan Media Big Book dalam Pembelajaran Membaca untuk Pemula Kelas 1 SD Tahfiz Qur’an Karimah T.A 2024/2025 - Khairu Annisa Pulungan; Fajar Sidik Siregar; Nurmayani Nurmayani; Fahrur Rozi; Putra Afriadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research was conducted to determine the feasibility, practicality, and effectiveness of big book media in reading learning for first-grade beginners of the Karimah Quran Memorization Elementary School, Berastagi. This research was R&D using the ADDIE development model. The subjects were 20 first-grade students. Data collection techniques included interviews, questionnaires, and tests. The instruments used in this study included interviews, expert instruments (tests, media, and materials), practical instruments (teacher response questionnaires), and student learning outcome tests. Data analysis techniques used in this study included qualitative and quantitative data. The results showed that the product's feasibility achieved a percentage of 85% and was categorized as feasible. The product's practicality score was 92%, categorized as very practical. The product's effectiveness score was 0.75, categorized as effective. It can be concluded that the use of Big Book as a reading medium for first-grade beginners at Tahfiz Quran Karimah Elementary School in Berastagi is feasible, practical, and effective.